Phlegmonous gastritis: Evolving from surgical to medical disease - Michael T. Czapka; Stephen J. Schrantz (IDCases, 2023)
We present a case of phlegmonous gastritis, which is a rare, life-threatening infection involving transmural inflammation of the stomach of multiple possible etiologies. Historically this disease has required surgical management, including gastrectomy, which is quite morbid. Evolving literature suggests that antimicrobial therapy alone may be adequate treatment for this infection. The diagnosis of phlegmonous gastritis was suggested by radiology but confirmed by endoscopic pathology. This particular case is unique given the patient’s age, lack of co-morbidities and being the first description of Helicobacter pylori with phlegmonous gastritis. We report on a specific successful antimicrobial regimen and duration of therapy, which has not been well documented elsewhere in the literature, which may be helpful to clinicians.